Learning te Reo Māori via Online Distance Education: A Case Study - Maree Jayne Jeurissen (Flexible Learning Association of New Zealand, 2015)
Despite some gains in the regeneration of te reo Māori, the indigenous language of Aotearoa New Zealand, its long-term survival remains threatened. One avenue for regeneration seldom considered is the English-medium secondary school. This article reports on a case study where students in one such school chose te reo Māori as an option and, and, because no face-to-face teacher was available, opted to continue via online distance education. Their experience over a year was documented and analysed through the lens of Willems' (2012) quadripartite model of resilience. Despite high levels of motivation, the students encountered considerable difficulties from which educators and education policy makers can learn important lessons.